Reinterpretación de la vivienda del siglo XXI en la arquitectura adaptable con el tiempo al interior de los espacios, caso de estudio Medellín Colombia (2023)
To design a place to live, you must take into account the houses that have been developed and what factors and spaces of these, has not been successful in the space to live. Factors that will be taken into account from various studies incorporated into the document, this will allow starting with an innovative design linked to the theme of adaptability so that each space in the house is effective according to the different needs that each space seeks. The project will be designed based on the selection of three locations which comply with the three climatic typologies that users may face, for the cold place Bogotá is selected, for the warm Barranquilla and temperate Medellín.